Myanmar Pay, Compensation, and Human Resource Management Review - World Bank (World Bank, Washington, DC, 2018)
The Myanmar Pay, Compensation and Human Resource Management Review was undertaken in 2015-2017 in response to the Government of Myanmar’s request for advice to inform compensation and human resource policies that reflect country-specific challenges. The analysis, generously supported by Denmark, Australia and UK-DFID, was jointly conducted by the Government of Myanmar and the World Bank.In addition to the analysis, the review aimed to develop capacity of government agencies responsible for wage-bill and human resource management. Capacity development happens within institutions, and can only be effective, if government assumes strong ownership. In this context, the Union Cabinet established the “Pay, Compensation, and Human Resource Review Implementation Inter-Ministerial Committee” comprising key ministries to oversee the review. The World Bank team worked closely with a task team in the Ministry of Planning and Finance.The main methods used to review the government’s pay and compensation system included: i) review of government regulations; ii) analysis of administrative data; iii) focus group discussions and a small survey to assess civil servants’ perception about pay and human resource functions; and iv) a model that simulates the impact of potential changes to pay and employment, customized to Myanmar’s circumstances. This model can be applied by the Ministry of Planning and Finance for future wage-bill planning. Specifically, the model helped highlight that size of the wage bill is not an immediate concern. Its rapid growth in recent years, as well as growing fiscal vulnerabilities from potential external shocks, demand closer attention to overall growth in the public-sector wage bill. Future salary increases may need careful targeting given the growing attractiveness of the private sector as a career option for young talent and professionals.The review also drills down on the education sector. Constituting nearly 40 percent of the total workforce employed by the Union Government, the education sector makes up nearly one-half of the union budget’s wage bill. The review also provides important context for teacher policy on employment and pay, and suggests reform options for managing teacher workforce for better education outcomes.The findings suggest a series of policy priorities for improving the performance of the civil service. The report includes a wealth of findings and practical, realistic recommendations. However, it is only the first step on the long journey of evidence-based reforms to manage wage bill and performance of the Myanmar civil service. The Government of Myanmar and the Bank will continue to work together during implementation of the recommendations, and for future research and analysis.